Autologous transplantation of deciduous tooth pulp into necrotic young permanent teeth for pulp regeneration in a dog model - Huang, Yan (J Int Med Res, 2019)
OBJECTIVES: To investigate the potential for pulpal regeneration via autologous transplantation of deciduous tooth pulp into immature necrotic permanent teeth using an experimental dog model. METHODS: Experimental apical periodontitis was induced in 60 teeth of six Beagle dogs. Following canal disinfection and pulpotomy, autologous deciduous pulp tissue was transplanted into the root canals (n = 30); as controls, contralateral teeth were treated in accordance with the recommendations of the American Association of Endodontists. Radiographic examinations were performed immediately before transplant, as well as 3 and 6 months after transplant. At the 6-month examination, root samples were collected and histological and immunohistochemical analyses were used to examine tissue regeneration. RESULTS: Radiographic analysis showed no significant differences in most histopathological parameters examined; however, apical diameter reduction was greater in the experimental group. Histological and immunohistochemical analyses showed that the canal walls of the experimental group had newly formed dentin-like tissue with dentinal tubules, while the control group had cementum-like deposits along the canal wall and apical foramina. CONCLUSIONS: Autologous transplantation may be useful for regeneration of dental pulp in necrotic young permanent teeth.